Nama dan Gelar di Keraton Yogyakarta - Sulistyawati Sulistyawati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2004)
One of the identities of the Yogyakarta palace community is their names and titles. The naming and entitlement system are influenced by kinship relation, rank in the palace, marital status of the partner of the nobility bearers, previous nobility status, and the working institution. The name and title are given to sultan's family and the abdi dalem (royal servants). There are two types of abdi dalem. The internal abdi dalem (abdi dalem punakawan) are employees who work inside the palace and the external abdi dalem (abdi dalem kaprajan) are those who apply for being